Design and implementation of a 200 to 1600 MHz, stepped frequency, ground penetrating radar transceiver - Farquharson, George (Department of Electrical Engineering, 2026)
This thesis project deals with the design and construction of a 200 to 1600MHz, stepped frequency, ground penetrating radar transceiver. This dissertation describes the system specifications of the radar, the design procedure used, the implementation of the radar transceiver. and measurements made to determine the performance of the transceiver. The dissertation briefly outlines the current state of ground penetrating radar technology. The system specifications of the transceiver are then developed and these are used to design the radar transceiver. The design considers various transceiver architectures, the synthesizer implementation using phase locked loops, and modification to the architecture for system phase coherence. The implementation of each of the transceiver modules is described showing specifications and specific designs for each. Laboratory measurements are made to measure the performance parameters of the transceiver and these are compared with the system specifications. The dissertation concludes with a summary of the work presented, a discussion on the performance of the radar with respect to the design and recommendations for the transceiver use and for future improvements. The major results and conclusions of the thesis are that a stepped frequency, ground penetrating radar transceiver module was designed and constructed and found to operate with the radar but that there was an insufficient accuracy in phase noise measurements to characterise the causes for the transceiver limitations completely. There were also unexplained spurious harmonics close to the carrier signal at high frequencies. Despite these limitations, most of thE" system specifications were achieved with the exception of the dynamic range and synthesizer phase noise and the transceiver dynamic range performance can be improved by limiting the frequency band to less than 800MHz. It was recommended that accurate measurements of thp phase noise be made and that the IF harmonic levels be investigated to ensure that they do not significantly affect the radar data. It was also stated that the radar be used over a reduced bandwidth to improve the dynamic range. II Abstract This thesis project deals with the design and construction of H. 200 to 1600MHz, stepped frequency, ground penetrating radar t,ranscciver. This disserl,ation describes the system spedfi e<t1ions of the radar, the design procedure used, til(' implementation of the radrt.r tra.nsceiver. and measurements made to determine the performa.nce of the transceiver. The dissertation brieHy outlines t he current slate of ground penetrating radar technology. The system specifications of the transceiver are then developed and these are used to design the radar transceiver. The de;ign considers variolls transceiver architectures, the synt.hesizcr implementation llsing phase locked loops, and modification to the architectU[e for system phase coherence. The implementation of each of the tra nsceiver modules is described showing specifications a.nd specific designs for each. Laboratory measul'enwnt$ are made to measure the performa nce pa.rameters of the transceiver and these arc compa.red with the system specifications. The dissertation concludes with a summary of the work presented, a discussion on the performance of the radar with respect to the design and recommcnda· tians for t he transcf'iver use and far fuLurc impravclllelits. The major results and conclusions of the thesis arf' that a stepped frequency, ground peneLra~ing radar transceiver module was designed and constructed and found to operate with the radar but thaI there was all insufficient accuracy in phase naise measurements to characterise the causes for the transteiver limitations completely. There were also unexplained spmious harmonics clo5e to the carrier signal at high frequencies, Despite these im~ itations, most of thl' system specifications were achieved with the exception of the dynamic range and synthesizer phase noise a nd the transceiver dynamic. range performance can be improved by limiting [he frequency band to less tha.n SOOMHz. It was recommended that accurate measurements of thp phase noise be made and that the IF harmonic levels be investigated to ensure that they do not significantly aflcr.t the radar data. It was a lso stated that till" radar be used over a reduced hand width to improve the dyna tnic range.